2000
DOI: 10.1039/b000166j
|View full text |Cite
|
Sign up to set email alerts
|

Amines as leaving groups in nucleophilic aromatic substitution reactions. Part 4.1 σ-Adduct formation in the hydrolysis of 1-amino-2,4,6-trinitrobenzenes

Abstract: The kinetic study of the reaction of 2,4,6-trinitro-1-pyrrolidinobenzene 3, 2,4,6-trinitro-1-piperidinobenzene 1 and 1-morpholino-2,4,6-trinitrobenzene 2 was made in 1,4-dioxane-water mixtures at 25 ЊC. In all cases, several processes were observed, the slowest of them leading to the formation of picrate ion. The fastest processes involved the formation of σ complexes by addition of one or two HO Ϫ to unsubstituted ring positions and the ionisation of the 1 : 1 complex. Besides, for compounds 1 and 3, cis-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…7 We have demonstrated that in aqueous solutions cyclic amines like pyrrolidine, piperidine and morpholine can act as leaving groups in aromatic nucleophilic substitution reactions of 1-amino-2,4-dinitrobenzenes, 8 and 1-amino-2,4,6-trinitrobenzenes. 1,9 Imidazole can also act as a leaving group in a reaction with hydroxide ions, 10 and n-butylamine 11 from 2,4,6-trinitrobenzene derivatives and piperidine and n-butylamine from 2,4-dinitrobenzene derivatives. 12 In this paper we report on the kinetics of the reaction of N-n-butyl-2,6-dinitroaniline 1 in basic solution which, in addition to the substitution product of the alkyl amino group, 2,6-dinitrophenol 2, gives a cyclization product, namely 7-nitro-2-n-propyl-1H-benzimidazole 3-oxide 3.…”
Section: Introductionmentioning
confidence: 99%
“…7 We have demonstrated that in aqueous solutions cyclic amines like pyrrolidine, piperidine and morpholine can act as leaving groups in aromatic nucleophilic substitution reactions of 1-amino-2,4-dinitrobenzenes, 8 and 1-amino-2,4,6-trinitrobenzenes. 1,9 Imidazole can also act as a leaving group in a reaction with hydroxide ions, 10 and n-butylamine 11 from 2,4,6-trinitrobenzene derivatives and piperidine and n-butylamine from 2,4-dinitrobenzene derivatives. 12 In this paper we report on the kinetics of the reaction of N-n-butyl-2,6-dinitroaniline 1 in basic solution which, in addition to the substitution product of the alkyl amino group, 2,6-dinitrophenol 2, gives a cyclization product, namely 7-nitro-2-n-propyl-1H-benzimidazole 3-oxide 3.…”
Section: Introductionmentioning
confidence: 99%
“…The second key degradation pathway in basic conditions is a nucleophilic aromatic substitution (S N Ar) of the 2-nitro-substituted benzene with the hydroxyl group from NaOH [ 50 , 54 , 58 , 59 , 60 ], resulting in degradation product B2 ( 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to have an alternative way of measuring the degree of substitution by picryl groups in polyethylenimine, we investigated the possibility of hydrolytically removing the picryl groups and measuring the amount of picric acid liberated [11]. Preliminary experiments with N-picryldiethylamine showed that it was only hydrolysed under basic conditions.…”
Section: Attempted Measurement Of the Ddegree Of Substitution By Hydrmentioning
confidence: 99%